Os efeitos da descontinuidade das entradas de caixa numa empresa de construção civil de grande porte - Sousa, José Ribamar de Oliveira (2011)
This study is inserted in a topic that has current1y been calling much attention from financiaI literature. The main reason for this fact is that since the publication of the law number 1l.308 of July 13th , 2007 which made obligated the publication of cash flow instead of presenting the proof of origin as well as application of resources. The cash flow must be treated as a great management tool that allows identifying the way money circulates in the company, in other words, identifies the leveI of liquidity showing the financiaI position ofthe company in order to establish trends 00 eventual remaining or lack of resources. The cash flow is accomplished with the purpose of demonstrating how the ioputs and outputs of the company' s financiaI resources behaved in a given period. The careful study of the cash flow done not only enables the trend analysis but also works as base for projected cash flow planning. The main objective ofthe study is to analyze the amount of financiai losses over the period betweeo 1996 to 2008. The financiai losses that we have referred to occurred due to the late payment from the client making necessary an increase of the working capital, caused by the big difference in the term between the (ideal) projected cash cycle compared to the real cash cycle. The current work was accomplished in a large company in the civil construction sector. The work was performed aimed at comparing the projected cycle flow to the real cycle flow, determining, therefore, the amount of financiai losses which was of R$ 48,46 million updated for the end of the period that was analyzed representing a reduction in profitability of 3 %. Key words: Cash flow. Working capital. Projected cash cycle. Real cash cycle.